The Royal Clasrooms in Saragossa: the failure of a popular education - María Rosa DOMÍNGUEZ CABREJAS (Historia de la Educación, 2013)
The grammar classrooms in Saragossa, run by the Society of Jesus from 1609 to 1767 when the Jesuits were banished, were transformed into royal or public classrooms, which entailed a change. Their internal organization and future development was based on some legislation which discouraged the traditional control of the local institutions, thus favouring an attitude of complete passivity and lack attention from the local council and the university. This situation, together with their scarce economic endowment allowed for misuse and unrestraint on the part of some teachers who considered their teaching as a transitory stage for their personal curriculum. The process of decay suffered by Saragossa's public classrooms, especially by the grammar classrooms, and the solution some important local institutions offered, that the Escuelas Pías, a religious order, should take up the teaching in those classrooms, shows how difficult it was to shift from religious to lay teaching. As a consequence of this we can say that there was a total failure in the first attempt in public teaching, as we consider it at present.